A Place to Call Home: Amphibian Use of Created and Restored Wetlands. (4th January 2012) - Brown, Donald J.; Street, Garrett M.; Nairn, Robert W.; Forstner, Michael R. J.
Abstract : Loss and degradation of wetland habitats are major contributing factors to the global decline of amphibians. Creation and restoration of wetlands could be a valuable tool for increasing local amphibian species richness and abundance. We synthesized the peer-reviewed literature addressing amphibian use of created and restored wetlands, focusing on aquatic habitat, upland habitat, and wetland connectivity and configuration. Amphibian species richness or abundance at created and restored wetlands was either similar to or greater than reference wetlands in 89% of studies. Use of created and restored wetlands by individual species was driven by aquatic and terrestrial habitat preferences, as well as ability to disperse from source wetlands. We conclude that creating and restoring wetlands can be valuable tools for amphibian conservation. However, the ecological needs and preferences of target species must be considered to maximize the potential for successful colonization and long-term persistence.